28.1k views
1 vote
-8b+ 2 + 6b = -3b + 7

2 Answers

2 votes

Answer:

b = 5

Explanation:

to solve this you must first combine like terms

-8b + 2 + 6b = -3b + 7

combine (add) -8b and 6b

that makes -2b

-2b + 2 = -3b + 7

now add 3b to both sides to put b on one side

-2b + 2 + 3b = -3b + 3b + 7

b + 2 = 7

now subtract 2 to both side

b + 2 - 2 = 7 - 2

b = 5

that is your answer

User Pranav Darji
by
5.3k points
2 votes

Answer:

b = 5

Explanation:

Add 8b to both sides :

2+6b = 5b+7

Subtract 5b from both sides :

2+b = 7

Subtract 2 from both sides :

b = 5

Let's check :

-8(5) + 2 +6(5) = -3(5) + 7

-40 + 2 + 30 = -15 + 7

-38 + 30 = -8

-8 = -8

Correct

Hope this helped and have a good day

User Benjamin Lindqvist
by
5.0k points